2015
DOI: 10.1002/esp.3724
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic properties of concentrated flow of a bank gully in the dry‐hot valley region of southwest China

Abstract: To quantify spatiotemporal variation in hydraulic properties of bank gully concentrated flow, a series of scour experiments were run under water discharge rates ranging from 30 to 120 l min−1. Concentrated flows were found to be turbulent and supercritical in the upstream catchment area and downstream gully beds. As discharge increased, values of the soil erosion rate, Reynolds number (Re), shear stress, stream power, and flow energy consumption (ΔE) increased while values of the Froude number (Fr) and the Dar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
51
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 39 publications
14
51
2
Order By: Relevance
“…In terms of temporal variation, the Froude number was higher than 1 for the gully bed under each flow discharge but less than 1 for the catchment area at 60-180, 18-82, and 14-28 min, with Froude number values This result was attributed to the fact that no increasing trend was observed among flow velocity with increasing flow discharge; however, the runoff depth increased due to the well development gully, especially under relatively high flow discharge.The data analysis showed that the flow velocity in these periods were 0.91-1.12, 0.84-1.05, and 1.03-1.22 times the value of the mean flow velocity, while the runoff depth was 1.10-1.42, 0.72-1.2, 1.15-1.31 times the mean runoff depth, respectively. The reason for the discrepancy with this study may be that the flow discharge inSu et al (2015) was 1.8 m 3 hr −1 and the gully height was 0.7 m, while the gully bed was 2 m. The lower flow discharge and gully height decreased the flow energy. In contrast, F I G U R E 1 2 Flow energy consumption at gully head and at total plots under different flow discharges F I G U R E 1 3 Sediment discharge under different flow dischargesSu et al (2015) found that Froude number far exceeded 1 in the catchment area but was less than 1 in the gully beds under 1.8 m 3 hr −1 in the dry-hot valley region of China.…”
contrasting
confidence: 78%
See 3 more Smart Citations
“…In terms of temporal variation, the Froude number was higher than 1 for the gully bed under each flow discharge but less than 1 for the catchment area at 60-180, 18-82, and 14-28 min, with Froude number values This result was attributed to the fact that no increasing trend was observed among flow velocity with increasing flow discharge; however, the runoff depth increased due to the well development gully, especially under relatively high flow discharge.The data analysis showed that the flow velocity in these periods were 0.91-1.12, 0.84-1.05, and 1.03-1.22 times the value of the mean flow velocity, while the runoff depth was 1.10-1.42, 0.72-1.2, 1.15-1.31 times the mean runoff depth, respectively. The reason for the discrepancy with this study may be that the flow discharge inSu et al (2015) was 1.8 m 3 hr −1 and the gully height was 0.7 m, while the gully bed was 2 m. The lower flow discharge and gully height decreased the flow energy. In contrast, F I G U R E 1 2 Flow energy consumption at gully head and at total plots under different flow discharges F I G U R E 1 3 Sediment discharge under different flow dischargesSu et al (2015) found that Froude number far exceeded 1 in the catchment area but was less than 1 in the gully beds under 1.8 m 3 hr −1 in the dry-hot valley region of China.…”
contrasting
confidence: 78%
“…Once the rainfall was larger than the daily rainfall intensity threshold, headcut erosion was initiated. Therefore, an increase in runoff would accelerate the headcut erosion process (Bennett et al, 2000;Bennett & Casalí, 2001;Su et al, 2014Su et al, , 2015. Additionally, the runoff flushing capacity increases, and more energy is consumed to transport the soil particles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Su et al (2014) investigated temporal variations in bank gully morphology and headcut erosion rates in response to a range of concentrated flows in this region. At a specified initial headcut height and water discharge rate, Su et al (2015) found spatiotemporal variations in hydraulic properties from a bare gully catchment down to a gully headcut as well as correlations between flow energy consumption (DE) and soil erosion rates. Distribution of and factors influencing vegetation within a downstream gully bed has also been ascertained by data taken at the Yuanmou Gully Erosion and Collapse Experimental Station ).…”
Section: Introductionmentioning
confidence: 98%